Unexplored relationship of sleep disturbances linked to suicidal ideation and behavior in postural orthostatic tachycardia syndrome - Shafqat MN (Dove Medical Press, 2017)
Muhammad Nabeel Shafqat,1 Muhammad Aadil,2 Maria Shoaib31Department of Medicine, University of Medical Sciences “Serafin Ruiz de Zarate” Villa Clara (UCMVC), Villa Clara, Cuba; 2Department of Psychiatry, Rush University Medical Center, Chicago, IL, USA; 3Department of Medicine, Dow Medical College, Dow University of Health Sciences, Karachi, PakistanWe read with great interest the currently published article written by Pederson and Brook1 entitled “Sleep disturbance linked to suicidal ideation in postural orthostatic tachycardia syndrome”. Awareness of postural orthostatic tachycardia syndrome (POTS) has increased in recent years. However, sleep disturbance has not been thoroughly investigated as a cause of increased suicidal risk in patients with POTS. We would like to applaud the authors on conducting this novel cross-sectional study to understand and highlight the potential relationship between sleep disturbances and increased risk of suicide in patients suffering from POTS.1View the original paper by Pederson and Brook.